Enhanced photo-Fenton-like process over Z-scheme CoFe2O4/g-C3N4 Heterostructures under natural indoor light - Yao, Y.; Wu, G.; Lu, F.; Wang, Shaobin; Hu, Y.; Zhang, J.; Huang, W.; Wei, F. (Springer, 2016)
Low-cost catalysts with high activity and stability toward producing strongly oxidative species are extremely desirable, but their development still remains a big challenge. Here, we report a novel strategy for the synthesis of a magnetic CoFe2O4/C3N4 hybrid via a simple self-assembly method. The CoFe2O4/C3N4 was utilized as a photo-Fenton-like catalyst for degradation of organic dyes in the presence of H2O2 under natural indoor light irradiation, a green and energy-saving approach for environmental cleaning. It was found the CoFe2O4/C3N4 hybrid with a CoFe2O4: g-C3N4 mass ratio of 2:1 can completely degrade Rhodamine B nearly 100 % within 210 min under room-light irradiation. The effects of the amount of H2O2 (0.01–0.5 M), initial dye concentration (5–20 mg/L), solution pH (3.08-10.09), fulvic acid concentration (5–50 mg/L), different dyes and catalyst stability on the organic dye degradation were investigated. The introduction of CoFe2O4 on g-C3N4 produced an enhanced separation efficiency of photogenerated electron - hole pairs by a Z-scheme mechanism between the interfaces of g-C3N4 and CoFe2O4, leading to an excellent activity as compared with either g-C3N4 or CoFe2O4 and their mixture. This study demonstrates an efficient way to construct the low-cost magnetic CoFe2O4/C3N4 heterojunction as a typical Z-scheme system in environmental remediation.